2001
DOI: 10.1159/000047070
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Surface Properties in Preterm Infants with Pneumonia

Abstract: Congenital pneumonia in preterm infants is often associated with respiratory insufficiency requiring mechanical ventilation. This study was performed to show whether pneumonia in these infants is associated with an inhibition or deficiency of surfactant. The ratio of lecithin and sphingomyelin (L/S ratio) and minimal surface tension were determined in pharyngeal aspirates from 90 term born infants (healthy) and in tracheal aspirates from preterm infants with wet lung (n = 13), congenital pneumonia (n = 21) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…This disease is often associated with surfactant dysfunction and respiratory failure requiring mechanical ventilation (32,33). In those infants PLV could be considered an alternative to treatment with CMV, despite the less promising clinical results obtained with PLV in adult patients with ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is often associated with surfactant dysfunction and respiratory failure requiring mechanical ventilation (32,33). In those infants PLV could be considered an alternative to treatment with CMV, despite the less promising clinical results obtained with PLV in adult patients with ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…This may cause epithelial injury to the airways, leakage of proteinaceous fluid into the alveoli and interstitium, leading to surfactant deficiency or dysfunction. Data from a German study (9) suggest that respiratory insufficiency in pneumonia is most likely caused by inhibition of surface-tension-lowering properties of surfactant rather than by surfactant deficiency. Important predisposing factors in the evolution of pneumonia are immaturity, low birth weight, premature rupture of membranes, chorioamnionitis and factors associated with prolonged neonatal intensive care (2,8).…”
Section: Epidemiologymentioning
confidence: 99%
“…Rudiger et al reported that the lung effluent of these infants had disturbed surface properties despite a sufficient amount of surfactant [39]. Based on their findings, they proposed that surfactant therapy could be beneficial in these infants.…”
Section: Treatmentmentioning
confidence: 99%